Cyclic‐RGD penta‐peptides cRGDyK derivatized with cyclopentadienyl complexes of technetium and rhenium as radiopharmaceutical probes. (30th May 2017) - Nadeem, Qaisar; Shen, Yunjun; Warsi, Muhammad Farooq; Nasar, Gulfam; Qadir, Muhammad Abdul; Alberto, Roger
Abstract : The present study reports the syntheses of half‐sandwich complexes of the type [M(η 5 ‐C5 H4 CONH‐R)(CO)3 ] (M═Re, 99m Tc;R═cyclic RGD peptide (cRGDyK) for potential imaging of αv β3 integrin expression. The 99m Tc complex was prepared directly from the reaction of [ 99m Tc(OH2 )3 (CO)3 ] + with cRGDyK, doubly conjugated to Thiele's acid [(C5 H5 COOH)2 ] in water. This approach extends the viability of metal‐mediated retro Diels‐Alder reactions for the preparation of small molecules such as linear tripeptides to a more complex cyclic peptide carrying a [(η 5 ‐C5 H4 ) 99m Tc(CO)3 ] tag. The Diels‐Alder product [(C5 H5 CONH‐cRGDyK)2 ] was prepared from Thiele's acid via double peptide coupling. The Re‐complex [Re(η 5 ‐C5 H4 CONH‐cRGDyK)(CO)3 ] was obtained by attaching [Re(η 5 ‐C5 H4 COOH)(CO)3 ] directly to the N‐terminus of cRGDyK. The identity of the 99m Tc‐complex is confirmed by chromatographic comparison with the corresponding rhenium complex, fully characterized by spectroscopic techniques. Abstract : In this paper, the concept of metal‐mediated retro ‐Diels‐Alder reaction was extended to more complex biomolecules such as cyclic RGD peptides. The technetium complex, [ 99mTc (η5‐C5 H4 CONH‐cRGDyK)(CO)3 )] was obtained by directly radiolabeling the precursor, namely, the penta‐peptide cRGDyK, doubly conjugated to Thiele's acid. Direct labeling in one step from [ 99m TcO4 ] − by microwave heating lead to the desired tracer in greater yields as compared to labeling by thermal heating.